A Survey to Assess Oral Hygiene Awareness, Difficulties Faced and Satisfaction Level During and after Orthodontic Treatment - Vignesh Kamath; Vinay Guggari; Amol Sangewar; Harsha Hegde; Priya Mukherjee; Swapna Bettanapalya Venkatesh; Smitha Sammith Shetty (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The foremost goal of orthodontic treatment is to improve dental occlusion and alignmentof teeth, which eventually results in a healthy functioning of dentition and facial aesthetics. The aim of thepresent study was to assess the oral hygiene awareness, difficulties faced and satisfaction level among agroup of students undergoing orthodontic therapy during and after treatment.Materials and Methods: A sample of 200 students from Melaka Manipal Medical College, who receivedorthodontic treatment were included in the study. A cross - sectional study in the form of self-administeredquestionnaire was carried out. The questions were based mainly to assess the difficulties faced, awarenesswith regard to oral hygiene and satisfaction level of the participants during and after orthodontic treatment.Results: The difficulties faced by orthodontics patients were in the range of 65 to 85%, which were troublesleeping, food lodgement and difficulty in maintaining oral hygiene. Study participants were not aware ofvarious cleaning modes though more than 50% used floss. In the post treatment phase, aesthetic appearancewas found to be better.Conclusion: The present study showed that the participants who were undergoing orthodontic treatment didnot have sufficient knowledge about oral hygiene practices. The participants were satisfied with the aestheticappearance post treatment.